Prevalence of resistant hypertension and associated factors in Japanese subjects with type 2 diabetes. Issue 1 (October 2015) - Yokoyama, H.; Araki, S.; Watanabe, S.; Honjo, J.; Okizaki, S.; Yamada, D.; Shudo, R.; Shimizu, H.; Sone, H.; Haneda, M.
Highlights The prevalence of treatment resistant hypertension is unclear in diabetes. This was estimated by mean values of office blood pressure over one year. It was evaluated with a high achievement of BP goals and adequate adherence. It was associated with cardiovascular risks and familial predisposition to hypertension. Treatment resistant hypertension is common and important in diabetes.